The Economic Determinants of Civil Unrest: A Cross-National Study - Moubarak, Ruba (Université d'Ottawa | University of Ottawa, 2014)
The issue of civil unrest is of tremendous importance for the successful implementation of economic and social policies. The last five years have shown that civil unrest can have far-reaching outcomes; removing governments from power to ending an increase in tuition fees. The phenomenon is common to developing and industrialized countries. This study assesses the economic factors to civil unrest by examining the behavior of 57,026 individuals across 43 countries. Data is retrieved from the 2005-2008 wave of the World Values Survey (WVS), the corresponding Freedom House Gastil Index, and country level macro data from the World Bank Tables. Binary logistic and probit regression models reveal the role of inflation, unemployment, income, economic growth, education and civil freedom on the likelihood of participating in civil unrest. The findings reveal a varying impact of these variables among developing and industrialized countries.